Increased persistence of lung gene expression using plasmids containing the ubiquitin C or elongation factor 1alpha promoter. - Gill, DR; Smyth, SE; Goddard, C; Pringle, I; Higgins, C; Colledge, W; Hyde, S (2001)
For effective gene therapy of chronic disease, persistent transgene expression at therapeutic levels is required. Clinical studies of airway gene transfer in patients with cystic fibrosis (CF) have resulted in short-lived transgene expression. We used intra-nasal dosing of naked plasmid DNA to the murine lung as a model for investigating the duration of airway gene transfer from a series of reporter expression plasmids. Transgene expression was transient when mediated by the viral promoters CMV, RSV and SV40, falling to less than 10% of peak expression after 2 weeks, although the presence of the adenoviral E4ORF3 gene in cis, resulted in extended duration of reporter activity from the CMV promoter. Transient expression from these promoters was not due to loss of the vector as determined by quantitative TaqMan PCR analysis. However, use of the promoters from the human polybiquitin C (UbC) and the elongation factor 1alpha (EF1alpha) genes resulted in persistent gene expression in the mouse lung. The UbC promoter directed high-level reporter activity which was maintained for up to 8 weeks and was still detectable 6 months after a single administration. Such persistent airway transgene expression from a nonviral vector without the concomitant expression of a potential antigen has not been reported previously. Thus, despite the persistence of vector DNA in vivo, attenuation of promoter function may lead to silencing of transgene expression and careful selection of promoter sequences is recommended for in vivo gene transfer.